2006
DOI: 10.1042/bj20061432
|View full text |Cite
|
Sign up to set email alerts
|

Big roles for small GTPases in the control of directed cell movement

Abstract: Small GTPases are involved in the control of diverse cellular behaviours, including cellular growth, differentiation and motility. In addition, recent studies have revealed new roles for small GTPases in the regulation of eukaryotic chemotaxis. Efficient chemotaxis results from co-ordinated chemoattractant gradient sensing, cell polarization and cellular motility, and accumulating data suggest that small GTPase signalling plays a central role in each of these processes as well as in signal relay. The present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
156
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(157 citation statements)
references
References 213 publications
(295 reference statements)
1
156
0
Order By: Relevance
“…RasGRF2 promotes exchange activities on both Ras and Rac GTPases (34); activation of either pathway can have profound effects on actin remodeling and cancer cell migration (35). A recent study showed that RasGRF2 regulates cancer cell invasion through direct binding to Cdc42 thereby sequestering it from association with cognate GEFs, and knockdown of RasGRF2 increased rounded invasion of melanoma cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…RasGRF2 promotes exchange activities on both Ras and Rac GTPases (34); activation of either pathway can have profound effects on actin remodeling and cancer cell migration (35). A recent study showed that RasGRF2 regulates cancer cell invasion through direct binding to Cdc42 thereby sequestering it from association with cognate GEFs, and knockdown of RasGRF2 increased rounded invasion of melanoma cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Candidates for such regulatory roles include members of the Rho-GTPase family of molecules, such as Rho and Rac1, which translate external signals into alterations in cytoskeletal reorganization and hence have the ability to influence migration. A large body of literature has characterized the cellular mechanisms and signal transduction pathways of Rho, Rho-dependent kinase (ROCK) and related regulatory members, such as Rac and PI3K, on cellular motility and chemotaxis in various cell types [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The small G-proteins, Cdc42, Rac and Rho, seem to be at the heart of the initial signals leading to the polarization of migrating cells (Charest and Firtel, 2007). They participate in cell migration by regulating cytoskeletal reorganization, a prerequisite for cell motility (Etienne-Manneville and Hall, 2002;Charest and Firtel, 2007).…”
Section: Cell Polarity Is Essential In Cell Migrationmentioning
confidence: 99%